Maternal western-style diet enhances the effects of chemically-induced mammary tumors in female rat offspring through transcriptome changes - Grassi, Tony Fernando [UNESP]; Bidinotto, Lucas T.; Lopes, Gisele A.D. [UNESP]; Zapaterini, Joyce R. [UNESP]; Rodrigues, Maria A.M. [UNESP]; Barbisan, Luís F. [UNESP] (Elsevier, 2019)
Previous studies have shown that early life intake of high-fat diet or western-style diet (WD) enhances the development of mammary tumors in adult female rats. Thus, we hypothesized that maternal WD throughout pregnancy and the lactation period could speed up the development of MNU-induced mammary tumors and alter their gene expression. For this, the present study investigated the gene expression profile of chemically-induced mammary tumors in female rat offspring from dams fed a WD or a control diet. Pregnant female Sprague-Dawley rats received a WD (high-fat, low-fiber and oligoelements) or a control diet from gestational day 12 until post-natal day (PND) 21. At PND 21, female offspring received a single dose of N-Methyl-N-Nitrosourea (MNU, 50 mg/kg body weight) and were fed a control diet for 13 weeks. Tumor incidence, multiplicity, and latency were recorded and mammary gland samples were collected for histopathology and gene expression analysis. Tumor multiplicity and histological grade were significantly higher and tumor latency was lower in WD offspring compared to control offspring. Transcriptome profiling identified 57 differentially expressed genes in tumors from WD offspring as compared to control offspring. There was also an increase in mRNA expression of genes such as Emp3, Ccl7, Ets1, Abcc5, and Cyr61, indicative of more aggressive disease detected in tumors from WD offspring. Thus, maternal WD diet increased MNU-induced mammary carcinogenesis in adult female offspring through transcriptome changes that resulted in a more aggressive disease.
Keywords: Adult female rats; Mammary tumor development; Maternal western-style diet; N-methyl-N-nitrosourea; Tumor gene expression